It’s a ‘two-way street’: resident perspectives of effective coaching relationships in the clinical learning environment - Trier, Jessica; Turnnidge, Jennifer; McGuire, Cailie S; Côté, Jean; Dagnone, J Damon (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Background: Coaching has gained traction in postgraduate medical education to enhance interactions between residents and clinical teachers, but these relationships present unique challenges and tensions. In order to realize the promises of coaching in medical education, we must understand how coaching relationships can be enacted to optimize resident development. The purpose of this study was to explore residents’ perceptions of key characteristics for effective clinical teacher-resident (CT-R) coaching relationships. Methods: We conducted four focus groups and eight interviews with residents at a Canadian academic center. Using a social constructionist approach, focus groups and interviews were audio recorded, transcribed verbatim, and thematically analyzed. Results: Residents described three main characteristics that contributed to effective CT-R coaching relationships: safe, meaningful, and collaborative. Residents emphasized that these characteristics needed to be bidirectional in nature to be most effective, in that both the resident and clinical teacher embodied these characteristics. Conclusions: Residents identified that effective coaching relationships were shaped not only by clinical teacher behaviours, but importantly, the quality of the interpersonal relationship that was fostered. Thus, it is imperative to consider the bidirectional nature of the CT-R coaching relationship when striving to enhance resident development.